Socio-economic Factors Influencing Technology Adoption among Fishermen Operating Motorized Fishing Craft - Balasubramaniam, S.; Charles Jeeva, J.; Ashaletha, S. (Fishery Technology, 2025)
In Kerala, there are about 1.90 lakh active marinefishermen operating about 14 151 motorized fishingcraft. The investment pattern, number of fishingdays, fuel utilization and technological changes inthe motorized fishing sector during the recent yearsindicate the extent of investment on fishing units,the relationship between the extent of adoption oftechnologies and the corresponding annual income.This paper presents the results of a study conductedamong random samples of 33 fishermen respondentsin Thiruvananthapuram district and 31 fishermenrespondents in Alappuzha district operating8.4 m LOA motorized FRP craft. It is seen thatmonofilament gillnets for mackerel, sardine andother were mostly operated by the fishermen in theFRP craft. Single day fishing was practised and nightfishing was not undertaken by these respondents.The adoption behaviour scores explained the extentof adoption of various improved practices/technologiesand the variables influencing the technologyadoption were determined in the multiple regressionanalysis. The constraints such as poor landingcentre facilities, inadequate kerosene subsidy, inadequatedevelopmental/extension schemes, ever-increasingmaintenance costs, diminishing fish catches,ever-increasing fuel prices, occasional conflicts withthe mechanised boat operators, ineffective insurancecoverage, damages caused to the fishing gears bypuffer fishes, inadequate relief measures duringnatural calamities, financial constraints and excessivefishing capacity were reported as factorsinhibiting the adoption of sustainable fishingpractices.